Polymorphism in the Interleukin‐7 Receptor‐alpha and Outcome after Allogeneic Hematopoietic Cell Transplantation with Matched Unrelated Donor. (21st July 2013) - Shamim, Z.; Spellman, S.; Haagenson, M.; Wang, T.; Lee, S. J.; Ryder, L. P.; Müller, K.
Abstract: Interleukin‐7 (IL‐7) is essential for T cell development in the thymus and maintenance of peripheral T cells. The α‐chain of the IL‐7R is polymorphic with the existence of SNPs that give rise to non‐synonymous amino acid substitutions. We previously found an association between donor genotypes and increased treatment‐related mortality (TRM) (rs1494555G) and acute graft versus host disease (aGvHD) (rs1494555G and rs1494558T) after hematopoietic cell transplantation (HCT). Some studies have confirmed an association between rs6897932C and multiple sclerosis. In this study, we evaluated the prognostic significance of IL‐7Rα SNP genotypes in 590‐recipient/donor pairs that received HLA‐matched unrelated donor HCT for haematological malignancies. Consistent with the primary studies, the rs1494555GG and rs1494558TT genotypes of the donor were associated with aGvHD and chronic GvHD in the univariate analysis. The Tallele of rs6897932 was suggestive of an association with increased frequency of relapse by univariate analysis ( P  = 0.017) and multivariate analysis ( P  = 0.015). In conclusion, this study provides further evidence of a role of the IL‐7 pathway and IL‐7Rα SNPs in HCT.